Nurt antropologiczny i egzystencjalny we wczesnej twórczości Juliusza Słowackiego - Żbikowski, Piotr (Śląskie Studia Polonistyczne, 2012)
The article presents an anthropological and existential conception of world and man creation in early works by Juliusz Słowacki. The most characteristic feature of this conception is searching an identity of homo sapiens. What is shown here constitutes above all the convictions concerning the nature of man and the fate of the world, and their individual as well as individually-marked dimension typical of Słowacki’s works representative of the whole epoch.